Wear behavior of iron boride coating on AISI 4140 - Yilmaz, S. Osman; Teker, Tanju; Karatas, Selcuk (Maik Nauka/Interperiodica/Springer, 2016)
A new paste technique was established for making boronising coatings. This method gave iron boride coatings a unique wear and tear property something that was tested as a microstructural feature. The coats were acquired from obtained by transmission of boron molecules from ferrobor concentrates to steel surface. Boronising parameters were applied at temperatures between 1023 and 1248 K temperatures at time range 2-8 h. This process led to enhancement in the coat layer, thickness and microstructure. To assess the durability and strength of the resultant element, a tribometer in block-on-ring configuration was used with a pairing of 20, 40 and 60 Newton's at sliding speeds of 0.2-1.85 ms(-1). It was found that, the coats made at temperatures of 1173-1223 K for 8 h lasted as long as the coat existed. Once they coat got off, residues of the same brought body abrasion. If time taken to boronize was reduced to 4-6 h at temperatures of between 1073 and 1173 K, then wear of the coat became oxidative with no trace of cracks.
Keywords: Carbon-Steels; Nickel; Chromium; Mixture; Alloys; Fecrc; Speed; Feb